Kinetic Model of LiFePO4 Formation Using Non-Isothermal Thermogravimetric Analysis - Abdul Halim Abdul Halim; Widiyastuti Widiyastuti; Heru Setyawan; Sugeng Winardi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2014)
The formation reaction of LiFePO4 from decomposition of precursors LiOH, FeSO4.7H2O and (NH4)2HPO4 with mol ratio of Li:Fe:P=1:1:1 was investigated. The experiment was carried out by thermogravimetric differential thermal analysis (TG-DTA) method using nitrogen as atmosfer at a constant heating rate to obtain kinetic constant parameters. Several heating rates were selected, there are 5, 7, 10, 15, 17.5, 22.5 and 25 °C/min. Activation energy, pre-exponential factor and reaction order were taken using Kissinger method and obtained respectively 56.086 kJ/mol, 6.95×108 min-1, and 1.058. Based on fitting result between reaction model and experiment were obtained that reaction obeyed the three dimension diffusion model. © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)